Pathogenic microbiota in the oral and nasal cavity of healthy individuals as a potential source of infections - Hoang, Van Tong; Bui , Tien Sy; Nguyen, Phong Thau; Nguyen, Thanh Viet (Tạp chí Y học Thảm hoạ và Bỏng, 2023)
Oral microbiota is personalized and varied among human habitats. Detection and identification of pathogenic bacteria and fungi are considered as a strategy for the prevention and control of infectious diseases. To date, no studies have investigated the prevalence of bacterial pathogens and fungi in healthy individuals in Vietnam, particularly the ethnic minorities. This study aimed to evaluate the presence of aerobic bacteria and fungi in the oral and nasal cavities of Jrai healthy individuals in the Central Highland. Oral and nasal swab samples of 140 healthy Vietnamese were collected. Microbiological procedures were performed using standard techniques. A total of 220 bacterial isolates were identified. Of which, 10% (22/220) were potentially pathogenic species including Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii, Escherichia coli, Neisseria meningitidis, and Staphylococcus aureus. The most predominant bacteria family was Moraxellaceae (40%, 88/220), followed by Streptococcaceae (36.82%, 81/220). Fungi were not detected in all samples. The oral and nasal cavity of healthy individuals harbors high frequencies of bacterial pathogens, suggesting its potential role as a source for these species. These pathogenic bacteria constitute the threat of their spread and the development of general infections. Infectious microbiota from the oral and nasal cavity should be examined as a preventive screening to control infectious diseases.